A Review of Placenta and Umbilical Cord-Derived Stem Cells and the Immunomodulatory Basis of Their Therapeutic Potential in Bronchopulmonary Dysplasia - Chia, Wai Kit; Cheah, Fook Choe; Abdul Aziz, Nor Haslinda; Kampan, Nirmala Chandralega; Shuib, Salwati; Khong, Teck Yee; Tan, Geok Chin; Wong, Yin Ping (Frontiers in Pediatrics, 2021)
Bronchopulmonary dysplasia (BPD) is a devastating lung disorder of preterm infants as a result of an aberrant reparative response following exposures to various antenatal and postnatal insults. Despite sophisticated medical treatment in this modern era, the incidence of BPD remains unabated. The current strategies to prevent and treat BPD have met with limited success. The emergence of stem cell therapy may be a potential breakthrough in mitigating this complex chronic lung disorder. Over the last two decades, the human placenta and umbilical cord) haves gained increasing attention as a highly potential source of stem cells. Placenta-derived stem cells (PDSCs) and umbilical cord-derived stem cells (UCDSCs) display several advantages such as immune tolerance and are generally devoid of ethical constraints, in addition to their stemness qualities. They possess the characteristics of both embryonic and mesenchymal stromal/stem cells. Recently, there are many preclinical studies investigating the use of these cells as therapeutic agents in neonatal disease models for clinical applications. In this review, we describe the preclinical and clinical studies using PDSCs and UCDSCs as treatment in animal models of BPD. The source of these stem cells, routes of administration, and effects on immunomodulation, inflammation and regeneration in the injured lung are also discussed. Lastly, a brief description summarized the completed and ongoing clinical trials using PDSCs and UCDSCs as therapeutic agents in preventing or treating BPD. Due to the complexity of BPD, the development of a safe and efficient therapeutic agent remains a major challenge to both clinicians and researchers.